Banda escolar: um processo de desenvolvimento musical, educativo e social - Higino, Sarah (1994)
The paper analyses the Martins de Oliveira music learning method through the practice of the school band, the chorus and the orchestra ( embryo). To start, the musical movement in Volta Redonda is discussed from the appearange of music bands and the role taken by the Fundação Educacional de Volta Redonda Concert Band, as the core for this learning method. The different method stages and the aims are presented, and the results are checked using the impressions of students and fellow teachers. Finally, it is demonstrated that this method of music learning acts on the child individual and social formation helping him or her integrating with the family and the social group.